Decrement of Transcriptome Level in Epithelial Tight Junction Claudin and Occludin as an Epithelial-Mesenchymal Transition Signature for Colorectal Cancer Biomarker : - Shirkoohi, Reza; Ghoojaei, Maryam; Saffari , Mojtaba; Emamirazavi, Amirnader; Hashemi , Mehrdad (Galen Medical Journal, 2022)
Background: Colorectal cancer is a common and fatal disease worldwide with increasing diagnosed cases yearly. Moreover, about 90% of deaths associated with cancers occur due to metastasis, which overcomes tight junction proteins such as claudin and occludin. The present study aimed to evaluate the significance of claudin and occludin expression change in human colorectal cancer. Materials and Methods: In this case-control study, 38 colorectal cancer patients were compared with normal samples regarding the expression levels of claudin and occludin genes by polymerase chain reaction. Results: The expression levels of claudin and occludin significantly decreased in tumor samples compared to normal samples. Conclusion: The change in the expression level of the claudin and occludin genes could be considered an influential factor in turning normal healthy tissues into cancerous cells.